Analisis Penerapan Target Costing sebagai Sistem Pengendalian Biaya Produksi pada UD. Era Jaya Kota Sibolga - Bancin, Sri Maymunah; Pohan, Safriadi; Tambunan, Yenni Sofiana (Global Education Journal, 2023)
This study aims to implement Target Costing as a production cost control system at UD. Era Jaya City of Sibolga, using a quantitative descriptive approach. Descriptive analysis is used to provide an overview and detailed explanation of the problems studied. The results of this study are 1). The application of target costing to the Era Jaya Trading Business in Sibolga City can reduce production costs by up to 9% to 13% 2). Able to save production costs for making 2-door and 3-door cabinets of Rp. 96,620 and Rp. 159,119. 3). Successfully reduced production costs for 2 and 3 door cabinets, with a reduction in production cost of Rp. 92,620 and Rp. 159,119. The conclusion is that by applying target costing, Era Jaya Trading Enterprises, Sibolga City can save production costs by up to 9% to 13%, which acts as a means of controlling production costs in the manufacture of 2-door and 3-door cabinets without reducing the quality of production results, thus enabling increased profits. optimally by maintaining a competitive selling price in the market. The next researcher suggests considering the variation of variables associated with the implementation of target costing, and considering the use of kaizen costing and value engineering as additional cost control methods, to avoid repetition of previous studies. thereby enabling an optimal increase in profit by maintaining a competitive selling price in the market. The next researcher suggests considering the variation of variables associated with the implementation of target costing, and considering the use of kaizen costing and value engineering as additional cost control methods, to avoid repetition of previous studies. thereby enabling an optimal increase in profit by maintaining a competitive selling price in the market. The next researcher suggests considering the variation of variables associated with the implementation of target costing, and considering the use of kaizen costing and value engineering as additional cost control methods, to avoid repetition of previous studies.